2014
DOI: 10.1136/bmjopen-2013-004470
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis on human brucellosis incidence in mainland China: 2004–2010

Abstract: ObjectivesChina has experienced a sharply increasing rate of human brucellosis in recent years. Effective spatial monitoring of human brucellosis incidence is very important for successful implementation of control and prevention programmes. The purpose of this paper is to apply exploratory spatial data analysis (ESDA) methods and the empirical Bayes (EB) smoothing technique to monitor county-level incidence rates for human brucellosis in mainland China from 2004 to 2010 by examining spatial patterns.MethodsES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 26 publications
(36 reference statements)
9
35
2
Order By: Relevance
“…This trend is consistent with the profile of the whole nation [21, 22, 24, 31] and other northern provinces, such as the Inner Mongolia Autonomous Area [25] and Shandong Province [27]. Sero-prevalence studies have also indicated an increasing drift in both livestock (0.7% in 2005–2006, and 1.5% in sheep in 2009, 3.71% in 2014) and occupational population (13.3% in 2005–2006, 22.0% in 2007, and 22.8% in 2011) [18–20, 44].…”
Section: Discussionsupporting
confidence: 89%
“…This trend is consistent with the profile of the whole nation [21, 22, 24, 31] and other northern provinces, such as the Inner Mongolia Autonomous Area [25] and Shandong Province [27]. Sero-prevalence studies have also indicated an increasing drift in both livestock (0.7% in 2005–2006, and 1.5% in sheep in 2009, 3.71% in 2014) and occupational population (13.3% in 2005–2006, 22.0% in 2007, and 22.8% in 2011) [18–20, 44].…”
Section: Discussionsupporting
confidence: 89%
“…From the time series plot, it 199 could be inferred that: ①The human brucellosis incidence rate went up significantly 200 during the study period; ②There was an overall upward trend of the epidemic in the 201 south area (especially in southeastern provinces) while the northern provinces still 202 kept high records of incidence rates. This indicated that the pastoral areas were still 203 high epidemic areas while the incidence of human brucellosis also became more 204 intense in half pastoral areas and agricultural areas, which coincided with the 205 conclusion of Zhang et al [19]. As for the cluster analysis, the result indicated that these 31 provinces could be 209 classified into three clusters according to their incidence level and epidemic trend.…”
supporting
confidence: 61%
“…Anselin's Local Moran I shows the extent of spatial autocorrelation (20,(24)(25)(26): significantly positive values indicate that the township and neighboring townships were similarly high or similarly low (high-high or lowlow), whereas significantly negative values indicate that a township and the neighboring townships were dissimilar (high-low or low-high). In this study, we defined high-high and high-low townships as high-risk clusters for incidence of severe HFMD and proportion of severe HFMD cases; low-low and low-high townships were defined as low-risk clusters.…”
Section: Discussionmentioning
confidence: 99%